Peculiar features of magnetic and resistive transitions in partially crystallized La0.84Na0.16MnO3 films - Pan’kiv, L.; Tsmots, V.; Pan’kiv, I.; Tovstolytkin, A.; Matviyenko, A. (Видавництво Львівської політехніки, 2012)
The present work aims to study magnetic, electric, magnetoresistance and resonance properties of partially crystallized La0.84Na0.16MnO3 thin films. Peculiar behavior resulting from the wide-range coexistence of highly conductive ferromagnetic and weakly conductive paramagnetic phases has been analyzed. Based on the results of magnetic measurements and theoretical calculations, the dependence of the volume fraction of ferromagnetic phase, VFM, on temperature is calculated. The VFM values whereby electric resistance and magnetoresistance display maxima are determined.
Keywords: doped manganites; ultrathin films; paramagnetic and ferromagnetic phases; magnetic resonance; magnetic and electric parameters